Guillain-Barre Syndrome linked to SARS-CoV-2 infection – meta-analysis and literature review - Nikola Siekierko; Maja Żołnierek; Wiktoria Kotusiewicz; Mateusz Lewandowski; Grzegorz Bienia; Zuzanna Lubczyńska; Yevheniia Popravko; Jakub Świętochowski (Journal of Education, Health and Sport, 2023)
Background